Heat and Mass Transfer - Karwa, Rajendra (Springer Nature Singapore : Imprint: Springer, 2017)
This textbook presents the classical treatment of the problems of heat transfer in an exhaustive manner with due emphasis on understanding of the physics of the problems. This emphasis is especially visible in the chapters on convective heat transfer. Emphasis is laid on the solution of steady and unsteady two-dimensional heat conduction problems. Another special feature of the book is a chapter on introduction to design of heat exchangers and their illustrative design problems. A simple and understandable treatment of gaseous radiation has been presented. A special chapter on flat plate solar air heater has been incorporated that covers thermo-hydraulic modeling and simulation. The chapter on mass transfer has been written looking specifically at the needs of the students of mechanical engineering. The book includes a large number and variety of solved problems with supporting line diagrams. The author has avoided duplicating similar problems, while incorporating more application-based examples. All the end-of-chapter exercise problems are supplemented with stepwise answers. Primarily designed to serve as a complete textbook for undergraduate and graduate students of mechanical engineering, the book will also be useful for students of chemical, automobile, production, and industrial engineering streams. The book fully covers the topics of heat transfer coursework and can also be used as reference for students preparing for competitive graduate examinations. .